1986
DOI: 10.1002/cne.902430305
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cell body size, axon size, and signal conduction velocity for individually labelled dorsal root ganglion cells in the cat

Abstract: Measurements of cell body and peripheral and central axon sizes were made for primary sensory neurons outlined by the intracellular injection of HRP. Conduction velocities were also measured on the outlined processes.The sensory neurons were then subdivided into A and C cells on the basis of the conduction velocity of the impulses carried by the processes of these cells.Central processes of both A and C cells are smaller than the peripheral processes, but the size differential is greater for the C cells. For A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(128 citation statements)
references
References 39 publications
9
116
1
2
Order By: Relevance
“…3). The large-diameter population can be subdivided into intermediate-large and largest diameter groups (16). With this subdivision, the intermediate-large neurons (1,500 -2,100 m 2 ) were not reduced in diabetic animals, but the largest neurons (Ͼ2,200 m 2 ) were significantly reduced (by 43%).…”
Section: Resultsmentioning
confidence: 99%
“…3). The large-diameter population can be subdivided into intermediate-large and largest diameter groups (16). With this subdivision, the intermediate-large neurons (1,500 -2,100 m 2 ) were not reduced in diabetic animals, but the largest neurons (Ͼ2,200 m 2 ) were significantly reduced (by 43%).…”
Section: Resultsmentioning
confidence: 99%
“…Medium-size cells with ADP display functional properties of nociceptors, with IB 4 -positive immunoreactivity in both control and diabetic groups but enhanced responses to capsaicin only in diabetic rats Previous in vivo recordings with sharp electrodes have shown that many medium-size DRG cells belong to slowly conducting A␦ sensory fibers, most of which are high-threshold mechanoreceptors capable of sensing painful stimuli (Harper and Lawson, 1985;Lee et al, 1986;Gerke and Plenderleith, 2001;Fang et al, 2005). Although acute enzymatic dissociation allows patch clamping and studies of ion channels, functional identification of dissociated DRG cells based on conduction velocity is not feasible.…”
Section: Diabetes Alters Biophysical Properties Of Voltage-dependent mentioning
confidence: 99%
“…However, expression of T-type Ca 2ϩ current is more heterogeneous between large (Ͼ45 m in diameter), medium (32-45 m), and small (20 -30 m) DRG cells (Scroggs and Fox, 1992). Based on studies using intact DRGperipheral nerve preparations, it is generally thought that most small and some medium DRG cells contribute to nociception (Lee et al, 1986). Thus, we restricted our experiments to cells Ͻ45 m in diameter (n ϭ 295).…”
Section: T-rich Cells Represent a Novel Subtype Of Sensory Neuronsmentioning
confidence: 99%